Finance, institutions and economic development - Demetriades, Panicos; Law, Siong Hook (John Wiley & Sons, Ltd, 2006)
Using data from 72 countries for the period 1978-2000, we find that financial development has larger effects on GDP per capita when the financial system is embedded within a sound institutional framework. Moreover, we find that financial development is most potent in middle-income countries, where its effects are particularly large when institutional quality is high. Importantly, we also find that in low-income countries the influence of financial development is at its weakest; in these countries, more finance without sound institutions may not succeed in delivering long-run economic benefits. Copyright © 2006 John Wiley & Sons, Ltd.